EFFECT OF CONVECTION ON THE DIFFERENTIATION OF MANTLE MATERIAL - Bulashevich Yu.P.; Khachay Yu.V.; Fershtater V.B. (My University, 1989)
The mantle is a very complex physicochemical system, and one is forced to use simplified models to analyze the convection in it. We investigate a mathematical model of convection in a compressible mixture consisting of two components. The results indicate that if Mg2SiO4 and Fe2SiO4 are assumed to be the principal components of the mantle, then the iron content of magmas erupted near mid-ocean ridges and intracontinental rifts, which is high compared with magmas of island arcs and orogenic plate-junction regions, would suggest a predominantly thermally-driven mechanism of convection in the Mesozoic and present-day mantle. The Concentration-driven mechanism of convection apparently would require the opposite zoning of igneous products.
Keywords: Mesozoic; Mesozoic; Мезозой